Influencing Factors on Nurses' Hand Washing Compliance - Amalia, Linda; Sumartini, Sri; Sasmito, Priyo; Yulianingsih, Nengsih; Sutresna, Nina (PT Inovasi Pratama Internasional, 2024)
Poor hand washing of nurses and unhealthy hospital environments contribute to the occurrence of nosocomial infections. Nurses who do not wash their hands before and after the procedure can become an intermediary for infection in patients at the service site or hospital and spread various multi-resistant organisms. This research aims to identify nurses' hand washing compliance and related factors. A descriptive correlation design was conducted in a hospital in West Java. Data on nurse characteristics and hand washing compliance were taken using a five moments test questionnaire cross-sectionally among nurses using the total sampling method and analyzed univariately and bivariately using descriptive analysis and the chi square test. A total of 67 nurses were involved in this research, the majority of respondents were aged 25-35 years (43/64.2%), women (42/62.7%), had a bachelor's degree (36/53.8%), had worked less than 5 years (42/62.7%) , lack of knowledge (35/52.2%), and have a positive attitude (38/56.7%), generally do not comply with hand washing protocols (34/50.7%). The nurse's age is related to hand washing compliance (p 0.002 < α 0.05), while gender (p 0.242), education (p 0.534), length of work (p 0.874), knowledge (p 0.907), and attitude (p 0.397) have α value > 0.05. Nurses' hand washing compliance is still less than the target. Age is related to nurses' compliance in implementing hand hygiene. Meanwhile, gender, education, length of work, knowledge and attitudes are not related to nurse compliance. Efforts are needed to increase nurses' knowledge to increase nurses' compliance in washing hands.